A case of epilepsy in multiple sclerosis: Three-dimensional double inversion recovery sequences revealed cortical dysplasia. Issue 4 (August 2017) - Zimatore, Domenico S; Trentadue, Mirko; Castellaro, Marco; Ferlisi, Monica; Piovan, Enrico; Calabrese, Massimiliano
In epileptic patients with multiple sclerosis (MS), cortical lesions have been suggested to cause seizures. In brain magnetic resonance imaging (MRI), double inversion recovery (DIR) sequences are generally used to evaluate MS cortical disease burden. We present the case of a woman, diagnosed with MS, suffering from drug-resistant partial seizures initially attributed to MS. The patient underwent many MRI exams, but only by means of high-resolution three-dimensional DIR sequences was a focal cortical dysplasia discovered. The MRI findings and FDG-PET/CT supported the diagnosis. This case recommends the use of DIR sequences both in patients with suspect epileptogenic lesions not detected with routine MRI protocols and in epileptic patient with MS, before ascribing seizures to MS.